Benefits and harms of non-surgical and non-pharmacological management of osteoporotic vertebral fractures: A systematic review and meta-analysis - Bolton, Karen; Wallis, Jason A; Taylor, Nicholas F (Revista brasileira de fisioterapia (São Carlos (São Paulo, Brazil)), 2022)
•Exercise programs and rigid bracing reduce pain in people with vertebral fractures.•Exercise and bracing may not increase activity or quality of life after vertebral fracture.•Exercise is not associated with harm after vertebral fracture. Osteoporotic vertebral fractures affect a large number of older adults Systematically review evidence of the benefits and harms of non-surgical and non-pharmacological management of people with osteoporotic vertebral fractures compared with standard care (control); and evaluate the benefits and harms of non-surgical and non-pharmacological management of people with osteoporotic vertebral fractures compared with an alternative non-pharmacological, non-invasive intervention. Systematic review and meta-analysis of randomized controlled trials. Five electronic databases (CINAHL, EMBASE, MEDLINE, PUBMED, and COCHRANE) were searched. Eligible trials included participants with primary osteoporosis and at least one vertebral fracture diagnosed on radiographs, with treatment that was non-surgical and non-pharmacological involving more than one session. Twenty randomized controlled trials were included with 2083 participants with osteoporotic vertebral fractures. Exercise, bracing, multimodal therapy, electrotherapy, and taping were investigated interventions. Meta-analyses provided low certainty evidence that exercise interventions compared to no exercise were effective in reducing pain in patients with osteoporotic vertebral fractures (mean difference (MD)= 1.01; 95% confidence interval (CI): 0.08, 1.93), and low certainty evidence that rigid bracing intervention compared with no bracing was effective in reducing pain in patients with osteoporotic vertebral fractures (MD= 2.61; 95%CI: 0.95, 4.27). Meta-analyses showed no differences in harms between exercise and no exercise groups. No health-related quality of life or activity improvements were demonstrated for exercise interventions, bracing, electrotherapy, or multimodal interventions. Exercise and rigid bracing as management for patients with osteoporotic vertebral fractures may have a small benefit for pain without increasing risk of harm. PROSPERO registration number CRD42012002936